Multilingual metal music : sociocultural, linguistic and literary perspectives on heavy metal lyrics - Valijärvi, Riitta-Liisa; Doesburg, Charlotte; DiGioia, Amanda (Emerald studies in metal music and culture., 2020)
This multi-disciplinary book explores the textual analysis of heavy metal lyrics written in languages other than English including Japanese, Yiddish, Latin, Russian, Hungarian, Austrian German, and Norwegian. Topics covered include national and minority identity, politics, wordplay, parody, local/global, intertextuality, and adaptation.